Risk Factors or Predictors of Developing Ciprofloxacin, Trimethoprim/Sulfamethoxazole and Third Generation Cephalosporin Resistance in Escherichia coli Infections: A Systematic Review and Meta-Analysis - Deshwal PR; Reddy NS; Fathima R; Aggarwal M; Tiwari P (Current Research in Pharmaceutical Sciences, 2023)
The Centers for Disease Control and Prevention (CDC) estimates that by 2050, ten million people a year could be dying as a result of Anti-Microbial Resistance (AMR). An increase in resistance has been observed for trimethoprim/sulfamethoxazole followed by ciprofloxacin and third-generation cephalosporins in the management of Escherichia coli infections. To identify risk factors for ciprofloxacin (Cip-REC), trimethoprim/sulfamethoxazole (TMP/SMX-REC,) and third-generation cephalosporin (TGC-REC) resistance in Escherichia coli infection relative to controls patients. A systematic search of MEDLINE/PubMed and Embase databases identified case-control, cohort, and cross-sectional studies on risk factors for Cip-REC, TMP/SMX-REC, and TGC-REC-infected patients. A random-effects model was used to pool odds ratios (ORs) of developing resistant E. coli infection. This study was registered with PROSPERO (CRD42022297043). A total of 23 studies were included (9891 participants). Overall, 22, 8, and 11 risk factors were identified for developing Cip-REC, TMP/SMX-REC, and TGC-REC infections respectively. The prior antibiotic use [OR=3.19] reported high pooled ORs for Cip-REC infection. TMP/SMX-REC infection was associated with genitourinary abnormalities [OR=2.91]. Further analysis unveiled potential factors for TGC-REC infection; prior history of admission [OR=3.14] and hemodialysis [OR=2.20]. Prior antibiotic usage, genitourinary disorders, and admission history increase the risk of Cip-REC, TMP/SMX-REC, and TGC-REC infections. Modifiable risk factors may help prevent resistant E. coli infection.